PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP INFORMASI PENYEBARAN DAKWAH KEPADA MAHASISWA PROGRAM STUDI ILMU KOMUNIKASI UNIVERSITAS NEGERI JAKARTA - Maulina Larasati Putri; Vera Wijayanti Sutjipto; Marissa Puspita Sary; Latifah Firdausah; Yoandra Putri Amarawati (Kinesik, 2021)
Instagram is one of the social media that is widely used by various groups ranging from teenagers to adults, so that the information uploaded on Instagram can reach a wide audience. The concept in this study is Instagram Social Media as variable X and Information on the Spread of Da'wah as variable Y. The population in this study were students of the 2019 State University of Jakarta Communication Studies program, totaling 82 people. This research uses uses and gratification theory. This study uses quantitative methods and the data that has been obtained is processed and analyzed by testing the validity, reliability and bivariate. The results showed that the t-count value of 6.265 is higher than the t-table value of 2.017, the validity of the X and Y variables which are more than 0.5 and can be said to be valid and the reliability of the X and Y variables which are more than 0.6 and can be said to be reliable so that it can be It was concluded that Instagram social media had an effect on the media for spreading da'wah to students of Communication Studies, State University of Jakarta, batch 2019.